Legal Form of Relief Is Free Of Charge by the Person or Group of Advocate for the Poor (Study at Jurisdiction in Ex Residency of Cirebon) - Tofan Alamsyah; Gunarto Gunarto (Jurnal Daulat Hukum, 2020)
The problems of this study are: 1) forms of legal assistance free of charge given to the person or group of poor people in the Ex Residency of Cirebon, 2) challenges and solutions lawyers to provide legal assistance free of charge at the Ex Residency of Cirebon, 3) forms of legal protection given for free of charge that given to the person or group of poor people in the Ex Residency of Cirebon in the future.The method used by researchers is legal approach empirically and specification in this study were included descriptive analysis. Even sources and types of data in this study are primary data obtained from interviews with field studies members of the Police of the Police Ciwaringin and Secretary Untag Jaya, And secondary data obtained from the study of literature relating to the theory of justice and progressive law.Based on the results of research that form of legal aid free of charge is given to a person or a group of poor people in the Ex Residency of Cirebon, have been met by providing a list of advocates in the district police or through the Legal Aid Post (ZIP Bankum) in each court both the General and courts that exist in the jurisdiction of the Ex Residency of Cirebon. Problems were found in providing legal assistance free of charge to the poor, is not all lawyers enrolled in Posbakum and district police to and willing to help to the poor who need legal help; The solution needed is a regulation that requires all lawyers who have permits proceedings to register and willing to help the poor who need legal aid, and the obligation to serve as a form of professional advocate obligation to perform community service.Keywords: Legal Assistance Free of Charge; Advocate, Poor.